PERTANGGUNGJAWABAN PIDANA SELEBGRAM ATAS PROMOSI JUDI ONLINE DI MEDIA SOSIAL (Studi Putusan Nomor : 509/Pid.Sus/2024/PN. Srg) - Nissa, Rika Khairun; Hasuri, Hasuri (Universitas Labuhanbatu, 2025)
Online gambling is a dangerous phenomenon that occurs in society, this practice can cause unrest and other crimes. This study aims to explain the nature and elements of unlawful acts in the promotion of online gambling by celebrities, as regulated in Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions. In addition, this study is normative juridical in nature using secondary data sources that are processed qualitatively using a Legislation approach and other legal sources relevant to this study. The main results of this study indicate that based on Decision Number 509 / Pid.Sus / 2024 / PN.Srg, celebrity Bunga Resti Amalia was legally and convincingly proven guilty of fulfilling the elements in Article 27 Paragraph (2) in conjunction with Article 45 Paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions. In short, it can be concluded that Bunga Resti deliberately promoted online gambling on the ZIGZAGSLOT site and the DAM77 site through her personal Instagram page. For what he did, the Defendant was sentenced to 10 months in prison, as well as a fine and confiscation of evidence. Previously, the prosecutor demanded a prison sentence of 1 (one) year and 6 (six) months, this verdict is lighter than the demands.Keywords: Criminal Liability; Online Gambling Promotion; Celebgram